2017
DOI: 10.1016/j.riam.2016.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Fungal monitoring of the indoor air of the Museo de La Plata Herbarium, Argentina

Abstract: Both the non-viable and viable sampling methods were necessary to monitor the bio-aerosol load in the La Plata Herbarium. The indoor air of this institution seems to be reasonably adequate for the conservation of vascular plants due to the low indoor/outdoor index, low concentrations of air spores, and/or lack of indicators of moisture problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
1
1
0
3
Order By: Relevance
“…In addition, YUSM (yellow unsporulated septate mycelium) and C. cladosporioides presented the highest relative density in CP and CES, respectively. Similar fungal strains were reported by Mallo et al [26] for the city of La Plata in a study related to the presence of airborne fungi detected by various sampling methods. At the same time, Negrin et al [27] reported that Cladosporium sp.…”
Section: Fungal Isolation and Ecological Categorysupporting
confidence: 87%
“…In addition, YUSM (yellow unsporulated septate mycelium) and C. cladosporioides presented the highest relative density in CP and CES, respectively. Similar fungal strains were reported by Mallo et al [26] for the city of La Plata in a study related to the presence of airborne fungi detected by various sampling methods. At the same time, Negrin et al [27] reported that Cladosporium sp.…”
Section: Fungal Isolation and Ecological Categorysupporting
confidence: 87%
“…En el aire exterior fueron 22747 esporas m -3 en E1 y 4707 esporas m -3 en E2. Tanto las concentraciones del aire interior como las del exterior fueron superiores a los informes de otras investigaciones realizadas en el Museo de La Plata (Argentina), y en la Galería Nacional de Umbría (Italia), ambas en zonas urbanas, donde se utilizaron, al igual que en este estudio, una metodología volumétrica no viable (Nitiu et al 2016, Mallo et al 2017, Ruga et al 2019. Esto puede deberse a que las condiciones ambientales y la variabilidad de sustratos presente en zonas rurales pueden favorecer mejor el desarrollo de los hongos que en áreas urbanas (Adhikari et al 2004).…”
Section: Resultados Y Discusiónunclassified
“…Two isolation methods were used to recover the cultivable mycobiota associated with the moult of N. granulata inhabiting a brackish salt marsh in Campos del Tuyú National Park (Argentina), which were complementary because they revealed specific taxa. This fact can be closely related to the existence of specific limitations for each isolation method, being physiological requirements (including nutritional ones) the critical aspects such as suggested by Mallo et al (2017). In this sense, the washing technique has been suggested be far more efficient to isolate actively growing microfungi on isolation source (Cabello & Arambarri 2002).…”
Section: Discussionmentioning
confidence: 99%